Impacts of Future Climate and Land Use/Cover Changes on Water-Related Ecosystem Services in Changbai Mountains, Northeast China - Wang, Hebin; Wang, Wen J.; Wang, Lei; Ma, Shuang; Liu, Zhihua; Zhang, Wenguang; Zou, Yuanchun; Jiang, Ming (Frontiers in Ecology and Evolution, 2022)
Sustaining ecosystem services in alpine regions is a pressing global challenge given future accelerating environmental changes. Understanding how future climate change and land use/cover change (LUCC) drive ecosystem service will be important in this challenge. However, few studies have considered the combined effects of future climate change and LUCC on ecosystem services. We assessed water yield and soil retention services and their drivers in the Changbai mountains region (CBMR) from the 2020s to 2050s using the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) model and factor control experiments. Water yield decreased by 2.80% and soil retention increased by 6.14% over the 30 years. Climate change decreased water yield and increased soil retention, while LUCC decreased both water yield and soil retention. The interactive effects between climate change and LUCC had relatively small inhibitory effects on water yield and large facilitation effects on soil retention. Changes in water yield were mainly attributed to climate change, while soil retention was largely influenced by interaction. Our study highlights the individual and interactive contributions of future climate change and land use to ecosystem service in the mountains region, which can provide important information for informed future land management and policy making for sustaining diverse ecosystem services.